Optimization of the Shell Thickness of the ZnO/CdS Core-Shell Nanowire Arrays in a CZTS Absorber - Wang, Chonge; Drame, Boubacar; Niare, Lucien; Yuegang, Fu (International Journal of Optics, 2022)
Copper-zinc-tin-sulfide (CZTS) solar cells have now become a topic of interest in the solar power generation industry. These are used as an absorber in the zinc oxide (ZnO)/cadmium sulfide (CdS) core-shell nanowire arrays, in order to improve the performance of solar cells. The relationship between the average increase in absorption rates and CdS shell thickness (compared to the thin film) reveals that the optimum thickness with the maximum average absorption rate (39.95%) compared to thin film is 30 nm. The cells’ electrical and optical performance was significantly improved with the introduction of graphene between the ZnO and CdS layers. The shell thicknesses for a better performance of these nanowire solar cells were 30 and 40 nm, with almost the same open-circuit voltage, the similar short-circuit current density, and efficiency, which were 630 mV, 6.39 mA/cm2, and 16.8%, respectively. Furthermore, a minimum reflection of 40% was obtained with these same shell thicknesses.